1988
DOI: 10.4049/jimmunol.140.11.3971
|View full text |Cite
|
Sign up to set email alerts
|

Role of L3T4+ and LyT-2+ cells in experimental visceral leishmaniasis.

Abstract: In contrast to euthymic (nu/+) BALB/c mice, athymic nude (nu/nu) BALB/c mice fail to control the visceral intracellular replication of Leishmania donovani, do not generate the macrophage-activating lymphokine IFN-gamma, and show little or no granulomatous tissue response. To characterize the T cell requirement for successful defense against L. donovani, nude mice were first reconstituted with unfractionated nu/+ immune spleen cells, which readily conferred the capacity to control and eliminate visceral (hepati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 140 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Approximately one week after infection, recruited T cells accumulate in granulomas to become the predominant cell type (Stern et al, 1988). Although it was previously assumed that T cells were primed in the spleen and migrated to the liver to combat the infection, recent studies have shown that parasite-specific CD4 + T cells may be primed in other tissues and are sufficient to confer immunity (Engwerda and Kaye, 2000).…”
Section: Murine Models Of Experimental Visceral Leishmaniasismentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately one week after infection, recruited T cells accumulate in granulomas to become the predominant cell type (Stern et al, 1988). Although it was previously assumed that T cells were primed in the spleen and migrated to the liver to combat the infection, recent studies have shown that parasite-specific CD4 + T cells may be primed in other tissues and are sufficient to confer immunity (Engwerda and Kaye, 2000).…”
Section: Murine Models Of Experimental Visceral Leishmaniasismentioning
confidence: 99%
“…Although it was previously assumed that T cells were primed in the spleen and migrated to the liver to combat the infection, recent studies have shown that parasite-specific CD4 + T cells may be primed in other tissues and are sufficient to confer immunity (Engwerda and Kaye, 2000). Both CD4 + and CD8 + T cells are essential for granuloma formation (Stern et al, 1988). Still, whereas CD4 + T cells can be activated by both KCs and granulomaassociated dendritic cells (DCs) (Stanley and Engwerda, 2007), the activation of CD8 + T cells is restricted to KCs (Beattie et al, 2010).…”
Section: Murine Models Of Experimental Visceral Leishmaniasismentioning
confidence: 99%